Fear of coronavirus in intensive care nurses: A cross-sectional study - Dığın, Figen; Kızılcık Özkan, Zeynep; Güçlü, Fatma; Erol, Gözde (Journal of Surgery and Medicine, 2022)
Background/Aim: The COVID-19 pandemic has had negative effects on healthcare workers and caused burnout and psychosocial problems, endangering their mental health. This study aimed to reveal the COVID-19 fears of intensive care nurses during the pandemic. Methods: The data of this cross-sectional study were collected with the participation of 128 nurses working in the intensive care units of two public hospitals between October 2020 and November 2020. The Nurse Identification Form and the Fear of COVID-19 Scale were used in data collection. The online survey forms were delivered to the nurses through WhatsApp groups to protect the health of both researchers and participants during the COVID-19 pandemic. Results: The nurses’ mean COVID-19 fear scale score was found to be 22.7 (5.1). The mean scale scores differed at statistically significant levels, depending on the education status and the number of patients per nurse in one single shift (P<0.05). Conclusion: The COVID-19 pandemic is a cause of stress and fear for nurses and other healthcare workers. During the COVID-19 pandemic process, it is crucial to assess the fears and coping skills of intensive care nurses; the nurses should also be supported physiologically, psychologically, and sociologically. New studies are needed to reveal the effectiveness of support services related to emotion management and infection control in nurses.